2014
DOI: 10.1093/mnras/stu1511
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of protostellar disc mass measurements and the existence of fragmenting discs

Abstract: We couple non-magnetic, hydrodynamical simulations of collapsing protostellar cores with radiative transfer evolutionary models to generate synthetic observations. We then use these synthetic observations to investigate the extent to which a simple method for measuring protostellar disc masses used in the literature recovers the intrinsic masses of the discs formed in the simulations. We evaluate the effects of contamination from the surrounding core, partially resolving out the disc, optical depth, fixed assu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 75 publications
9
70
1
Order By: Relevance
“…E.g., for our baseline solar-type model, there are 20 accretion episodes, each of which has a f bin /20 ≈ 1.5% chance of forming a new companion. The accretion rates and stochastic variability of embedded Class 0 protostars are higher than their older Class I counterparts (Froebrich et al 2006;Krumholz et al 2009;Peters et al 2010;Dunham et al 2014;Hartmann et al 2016), and so fragmentation may preferentially occur during earlier episodes. To encompass this possibility, we consider a model Frag1 in which the probability of fragmentation is p ∝ t −0.5 , i.e., the first accretion episode at t = 0.1 is three times more likely to form a new companion than the last episode.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…E.g., for our baseline solar-type model, there are 20 accretion episodes, each of which has a f bin /20 ≈ 1.5% chance of forming a new companion. The accretion rates and stochastic variability of embedded Class 0 protostars are higher than their older Class I counterparts (Froebrich et al 2006;Krumholz et al 2009;Peters et al 2010;Dunham et al 2014;Hartmann et al 2016), and so fragmentation may preferentially occur during earlier episodes. To encompass this possibility, we consider a model Frag1 in which the probability of fragmentation is p ∝ t −0.5 , i.e., the first accretion episode at t = 0.1 is three times more likely to form a new companion than the last episode.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…The mass is calculated using the flux of the Gaussian and point source, i.e., F ps + F G , and assumes an average temperature of 30 K. This temperature could be lower, which would increase the mass (e.g., Jørgensen et al 2009;Dunham et al 2014) 3.3. Power-law disk…”
Section: Gaussian Intensity Distributionmentioning
confidence: 99%
“…Nevertheless, a lower value of Σ cr = 0.1 g cm −2 results only in a few percent increase in the net disk mass (see Fig. 2 in Dunham et al 2014a). We found that our algorithm generally works well, but may somewhat overestimate the disk mass in the early Class 0 stage (when the inner part of the infalling envelope may have densities exceeding Σ cr ) and somewhat underestimate the disk mass in the late Class I and Class II stages (when the disk spreads out and its density drops below Σ cr in the outer parts).…”
Section: Comparison Of Disk Propertiesmentioning
confidence: 99%